USA experience in priorities of security is a lesson for modern Ukraine - Zainchkovskyi, D. M.; Заінчковський, Д. М. (Актуальні питання розвитку сектору безпеки і оборони (зарубіжний досвід) : зб. тез доп. учасників ХХVІ Міжнар. наук.-практ. конф. інозем. мовами для здобувачів освіти (м. Вінниця, 4 квіт. 2025 р.). – Вінниця : ХНУВС, 2025. – С. 285-287, 2025)
Наголошено, що досвід США допоможе Україні створити скоординовану та ефективну систему реагування на кіберзагрози, що зрештою підвищить рівень національної безпеки.

It was emphasized that the experience of the United States will help Ukraine create a coordinated and effective system for responding to cyber threats, which will ultimately increase the level of national security.
Keywords: кібербезпека; кіберзагрози; США; зарубіжний досвід; cybersecurity; cyber threats; USA; foreign experience